우리나라 당뇨병성 족부질환의 현황: 건강보험자료 분석결과 - 정춘희; Choon Hee Chung; 김대중; Dae Jung Kim; 김재용; Jai Yong Kim; 김혜영; Hye Young Kim; 김화영; Hwa Young Kim; 민경완; Kyung Wan Min; et al. (Diabetes & metabolism journal, 2006)
연구배경: 당뇨병환자에서 족부궤양의 빈도는 비당뇨인 보다 높고 족부궤양 발생 시 절단의 발생률이 높으며 의료비용이 많이 드는 것으로 보고되고 있어 당뇨병 초기부터 철저한 혈당 관리가 필요함은 자명하다. 그러나 현재까지 국내에서는 이에 대한 근간이 되는 연구가 거의 전무한 상태로서 학회 차원의 대규모 역학 연구가 필수적이다. 방법: 저자들은 1994년 12월 1일부터 2002년 12월 31일까지 당뇨병을 주 또는 부상병으로 건강보험심사평가원에 1회이상 청구된 3,911,647명의 환자 중 사망자와 기존 유병자를 제외한 3,587,547명의 환자를 대상으로 2003년도의 당뇨병성 족부질환의 발생률과 의료비용을 알아보고자 본 연구를 시행하였다. 결과: 당뇨병환자 (391만 1647명)의 1.2%에서 족부질환이 있었으며 이는 전체 족부질환의 47.9%였고 이중 족부절단은 전체 족부절단의 54.4%, 족부궤양은 전체 족부궤양의 52.5%, 족부손상은 전체 족부손상의 11.7%였다. 당뇨병환자에서 인구 10만 명당 족부질환 발생률은 족부절단 49.7명, 족부궤양 99.7명, 족부손상 1,051명이며 비당뇨병환자에서는 각각 4.2명, 10.3명, 943명이었다. 비당뇨병과 당뇨병환자간의 족부질환 발생건수의 비교에서는 족부절단의 경우 당뇨병환자가 비당뇨병환자에 비해 11.7배, 족부궤양의 경우 9.7배, 족부손상의 경우 1.1배 많았다. 1인당 평균 총 진료비는 족부절단 1162만원, 족부궤양 780만원, 족부손상 354만원으로 비당뇨병환자에 비해 각각 2.0배, 1.7배, 2.1배 많았고 평균 입원일수는 족부절단 76일, 족부궤양 61일, 족부손상 33일로 비당뇨병환자에 비해 각각 1.6배, 1.3배, 1.7배 길었다. 결론: 당뇨병환자에서 비당뇨인에 비해 족부궤양 및 족부절단의 발생률이 매우 높음은 물론 의료비용이 매우 많이 소요됨을 알 수 있었다. 따라서 이를 줄이기 위해 보다 초기에 엄격한 당뇨병 관리는 물론 대국민차원의 홍보 및 국가차원의 관리가 필수적일 것으로 생각된다. Background: Foot ulcer diseases are more prevalent in diabetic patients than that those of non-diabetic patients. Several reports showed the risk of amputation and the medical cost were increased when foot ulcer developed. Therefore, strict glycemic control from the initial period of diabetes is necessary. Since there is no enough epidemiologic data, large scaled studies for medical and economic consequences about diabetic foot ulcer are needed. Methods: This study was based on health insurance claims submitted to the National Health Insurance Review Agency during the period from December 1994 through December 2002. We investigated the incidence and medical cost of foot disorders in Korean population using the disease-classification codes on the health insurance claim forms. Results: The incidences of foot disorders (per 100,000 of population) were 49.7 for amputations, 99.7 for ulcers, and 1,051 for injuries in diabetic patients, and 4.2 for amputations, 10.3 for ulcers, and 943 for injuries in non-diabetic patients. Relative risk of the incidences of foot amputation, ulcer, and injury in diabetic patients comparing with non-diabetic patients were 11.7, 9.7, and 1.1, respectively. Total medical costs (per capita) of foot amputation, ulcer, and injury in diabetic patients were 2.0, 1.7, and 2.1 times higher, respectively, than those of non-diabetic patients. Mean hospital stay of foot amputation, ulcer, and injury in diabetic patients were 1.6, 1.3, and 1.7 times more, respectively, than those of non-diabetic patients. Conclusion: In diabetic patients, the incidences of foot amputation and ulcer are higher than those of non-diabetic patients. To reduce those incidences, we need to early strict glycemic control as well as government based management. (J Kor Diabetes Assoc 30:372~376, 2006)